Curing the Megaplasmid pTT27 from Thermus thermophilus HB27 and Maintaining Exogenous Plasmids in the Plasmid-Free Strain - Ohtani, Naoto (Appl Environ Microbiol, 2016)
Stepwise deletions in the only plasmid in Thermus thermophilus HB27, megaplasmid pTT27, showed that two distantly located loci were important for maintenance of the plasmid. One is a minimum replicon including one gene, repT, coding a replication initiator, and the other encodes subunits of class I ribonucleotide reductase (RNR) for deoxynucleoside triphosphate (dNTP) synthesis. Since the initiator protein, RepT, bound to direct repeats downstream from its own gene, it was speculated that a more-downstream A+T-rich region, which was critical for replication ability, could be unwound for replication initiation. On the other hand, the class I RNR is not necessarily essential for cell growth, as evidenced by the generation of the plasmid-free strain by the loss of pTT27. However, the plasmid-free strain culture has fewer viable cells than the wild-type culture, probably due to a dNTP pool imbalance in the cell. This is because of the introduction of the class I RNR genes or the supplementation of 5′-deoxyadenosylcobalamin, which stimulated class II RNR encoded in the chromosome, resolved the decrease in the number of viable cells in the plasmid-free strain. Likewise, these treatments dramatically enhanced the efficiency of transformation by exogenous plasmids and the stability of the plasmids in the strain. Therefore, the class I RNR would enable the stable maintenance of plasmids, including pTT27, as a result of genome replication normalized by reversing the dNTP pool imbalance. The generation of this plasmid-free strain with great natural competence and its analysis in regard to exogenous plasmid maintenance will expand the availability of HB27 for thermophilic cell factories.